Smart Road Wireless Electric Vehicle Charging - Saurabh Prakash Moon; Vaibhav Kalse; Anuragh Nagar; Y.M. Patil (International Journal of Electrical Power and Machine Systems, 2024)
Interest in electric vehicles (EVs) has increased recently due to worries about global warming and the depletion of petroleum resources. It is recognized that having access to wireless charging while traveling and EV charging stations systems are necessary for EV adoption and widespread use. Smart roads for EV wireless charging using piezoelectricity is a novel technology that has the potential to revolutionize the transportation industry. With the use of piezoelectric materials, this technology transforms the kinetic energy of moving cars into electrical energy, which is then utilized to wirelessly charge electric vehicles' (EVs') batteries while they are in motion. One of the key advantages of this technology is that it can provide EVs with continuous charging, even while they are in motion. This eliminates the need for EVs to stop and plug in to charge, which can significantly reduce travel time and range anxiety.
Keywords: ESP32; EV: Electric Vehicle; Piezoelectric energy; Piezoelectric material; Smart Road; Wireless EV Charging; wireless charging